ANALISIS PERFORMANCE INVERTER FULL BRIDGE SATU FASA - Novitasari Novitasari; Bambang Sri Kaloko; Suprihadi Prasetyono; Moch Ghozali; Guido Dias Kalandro (Universitas Islam Lamongan, 2023)
Technological advances are increasingly rapid and cannot be separated from the use of electricity for various types of electronic devices that use electrical energy. The use of electrical energy cannot be separated from DC and AC energy sources. The electric voltage itself can be done by changing or converting electrical energy from DC to AC using an inverter. The inverter itself is a device that can convert DC voltage to AC with a full bridge configuration that uses a transformer to get the best efficiency using a transformer, using an input voltage of 12 VDC to get 220 VAC by changing the value of the duty cycle used to find the results of the PWM wave and get the efficiency value. From these experiments it was then tested with 15W and 30W loads to get good efficiency values and wave output results.